Evaluation of Career Development Programs from an Action Perspective - Young, Richard A.; Valach, Ladislav (Canadian Journal of Counselling and Psychotherapy, 2007)
An action-theoretical approach to the evaluation of career development programs is based on a constructionist epistemology and extends recent developments in the career and program development fields. Propositions for an action-theoretical perspective centre around career and action as related, interpretative constructs. These propositions give rise to implications and questions for the evaluation of career programs that address, among others, the ongoing nature of programs and career processes, and the social bases for career action that occurs in career programs.